Primary Gastrointestinal Tract Lymphoma - David Reinhard Sumantri Samosir; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2010)
Extranodular lymphomacanbe found in almostallorgan. One third of the cases found in gastrointestinal(GI) tract, whichisthemost commonformofextranodular lymphoma.All thesubtypesof lymphomamayoccurasprimarylesionalongingastrointestinaltract,butthemostcommonformis B-celldiffuse largecelllymphoma.DiseasesthatlinkedwithGItractlymphomaareinflammatorybowel disease, celiac disease,Helicobacter pylori, virus infection,collagen diseaseandionicradiation.This reportdescribed a40yearsoldmanwith recurrentbloodystoolandcolon lymphomawasblamedas the sourceofbleeding withitsmanagementoflymphoma. Keywords:lymphoma, gastrointestinaltract,extranodular